The 1977 Tundra Fire at Kokolik River, Alaska. - Hall,D; Brown,J; Johnson,L (1978)
During summer 1977 widespread fires occurred in northwest Alaska. Through the use of Landsat imagery and ground studies, one such fire, at Kokolik River, was examined. The Kokolik fire was first reported on 26 July, and by the time it was extinguished had consumed 44 sq km of tundra vegetation. Streams and drainages contained the fire on several sides. Ground observations provided information on the intensity of the fire effects. Depth of thaw by late August measured 35.4 cm in the burned areas and 26.6 cm in the unburned areas. (Author)